A marked decline in the incidence of malaria in a remote region of Malaita, Solomon Islands, 2008 to 2013 - Oloifana-Polosovai, Hellen (World Health Organization, 2014)
SETTING: Atoifi Adventist Hospital (AAH), Solomon Islands, the only hospital in the East Kwaio region. OBJECTIVE: To use routine surveillance data to assess the trends in malaria from 2008 to 2013. DESIGN: Descriptive study of records from (1) AAH laboratory malaria records; (2) admissions to AAH for malaria; and (3) malaria treatments from outpatient records. RESULTS: AAH examined 35 608 blood films and diagnosed malaria in 4443 samples comprised of 2667 Plasmodium falciparum (Pf) and 1776 Plasmodium vivax (Pv). Between 2008 and 2013 the total number of malaria cases detected annually decreased by 86.5%, Pf by 96.7% and Pv by 65.3%. The ratio of Pf to Pv reversed in 2010 from 2.06 in 2008 to 0.19 in 2013. For 2013, Pf showed a seasonal pattern with no cases diagnosed in four months. From 2008 to 2013 admissions in AAH for malaria declined by 90.8%, and malaria mortality fell from 54 per 100 000 to zero. The annual parasite index (API) for 2008 and 2013 was 195 and 24, respectively. Village API has identified a group of villages with higher malaria incidence rates. CONCLUSION: The decline in malaria cases in the AAH catchment area has been spectacular, particularly for Pf. This was supported by three sources of hospital surveillance data (laboratory, admissions and treatment records). The decline was associated with the use of artemisinin-based combined therapy and improved vertical social capital between the AAH and the local communities. Calculating village-specific API has highlighted which villages need to be targeted by the AAH malaria control team.